Teaching immigrant students: Finnish teachers' understandings and attitudes - Vigren Heli; Alisaari Jenni; Heikkola Leena Maria; Acquah Emmanuel; Commins Nancy (Elsevier, 2022)
This study analysed Finnish teachers' (N = 820) understandings and attitudes about teaching students from immigrant backgrounds and how these relate to linguistically and culturally responsive education. The data were gathered via an online-survey in 2016. The results indicate that the Finnish teachers surveyed had knowledge about second language acquisition, had positive attitudes towards students' first languages, and had a strong sense of responsibility to promote equity and social justice. However, there were specific areas in which teachers lacked knowledge and demonstrated uncertainty about teaching students with immigrant backgrounds. These findings provide guidance for the improvements in teacher education.